Influence of volume of endodontic irrigants used in different irrigation techniques on root canal dentin microhardness - Buvaneshwari Arul; Nandini Suresh; Ranjithkumar Sivarajan; Velmurugan Natanasabapathy (Wolters Kluwer Medknow Publications, 2021)
Introduction: Overzealous application of endodontic irrigants affects the root canal dentin mechanical properties. The effect of volume of endodontic irrigants on the microhardness of root canal dentin has not been studied. Aim: This study assessed the effect of volume of endodontic irrigants used in different final irrigation activation techniques on root canal dentin microhardness (RCDM). Methodology: Sixty human maxillary central incisors were embedded in acrylic resin in Kuttler's endodontic cube to the level of cementoenamel junction. The root samples were randomly divided into 4 experimental groups (n = 15): Group-NI-needle irrigation, Group-PUI-continuous passive ultrasonic irrigation, Group-EndoVac-apical negative pressure system, Group combination- EndoVac + PUI irrigation. Root canals were instrumented up to size 40 (F4). The resin mounted specimens were sectioned longitudinally into two halves and were reassembled in Kuttler's kube to carry out final irrigation activation. A predetermined standardized volume of irrigants was used in each group. The RCDM was measured after root canal instrumentation and after final irrigation using Vicker microhardness tester (coronal, middle, and apical third). The reduction in RCDM values (p < 0.0086) were analyzed using Kruskal Wallis and Mann Whitney-U tests. Results: Reduction in RCDM was observed with all the endodontic irrigating techniques tested. EndoVac and combination irrigation techniques showed maximum reduction in RCDM in all thirds of root canal. Conclusion: It is concluded that the volume of irrigants and agitation plays a role in reducing RCDM. The overall volume of irrigants to cause maximum reduction was 25 ml, beyond which neither volume nor agitation affects RCDM.